The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.matchar.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Strain localization in Ti-6Al-4V Widmanstätten microstructures produced by additive manufacturing

Abstract: Although Additive Manufacturing (AM) offers numerous performance advantages over existing methods, AM structures are not being utilized for critical aerospace and mechanical applications due to uncertainties in their structural integrity as a result of microstructural variations and defects arising from the AM process itself. With strain localization serving as a precursor for material failure, the impact of microstructural variations in Direct Metal Laser Sintering (DMLS) produced Ti-6Al-4V on strain localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…It has also been shown that there is not a correlation between the Schmid factor and high strain values measured by DIC in FCC materials [35]. On the other hand, Schmid law has been shown to be satisfactory to explain slip system activation in Ti-6Al-4V [14,36] and good correlation in the present study is also observed. Surface topography studies ( Fig.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…It has also been shown that there is not a correlation between the Schmid factor and high strain values measured by DIC in FCC materials [35]. On the other hand, Schmid law has been shown to be satisfactory to explain slip system activation in Ti-6Al-4V [14,36] and good correlation in the present study is also observed. Surface topography studies ( Fig.…”
Section: Discussionsupporting
confidence: 60%
“…High prismatic and basal Schmid factors also show good correlation with strain localization in the high aspect ratio ′ and ′ colonies respectively. However, correlation between strain localization in high aspect ratio ′ and high basal Schmid factor has also been reported in the literature [14]. At room temperature, the prismatic slip system in the α-Titanium displays the lowest critical resolved shear stress [32].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In [31], tensile tests conducted with DIC at a macroscopic level underlines the fact that the existence of a microstructure gradient induces strain localization. Otherwise, other works use DIC at a smaller scale to highlight spatial distribution of strain within grains [4,7,9,29]. However, no study could be found where DIC is conducted at grain level in repaired microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to provide wide complex of researches and tests. Titanium alloys are used in the following additive technology: melting layer by layer powder by electron beam (EBM) [1,2] or laser (SLM, SLS methods) [3,4], feeding melted powder or wire by plasma arc [5,6] or laser (DMLD) [7,8]. We suggest using laser metal deposition technology for manufacturing of titanium parts.…”
mentioning
confidence: 99%